Historical traditions of democracy in Ukraine - Stechyshyn A. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of our research is to highlight the patterns and traditions of people’s rule in Ukraine Method. The methodology includes the complex use of a problem-chronological approach, as well as hermeneutic, formal-legal, formal-historical, and critical methods. Results. It has been established that people’s power acts as a condition and one of the forms of existence of the state and institutions of power. The tradition of people’s rule in Ukraine is considered in accordance with its two classic forms – direct or direct people’s rule (direct democracy) and indirect or indirect (representative democracy). For the Ukrainian state-legal tradition, direct people’s power is traditional and possibly belongs to the norms of legal custom. For example, a manifestation of direct people’s rule was a viche in the Old Russian state or a Cossack council in the times of the Hetmanship. With regard to the powers of the vicha and the Cossack Council, they were quite close and, in general, maximal for their time. The main regulatory act regulating the procedure of direct people’s power is the Constitution of Ukraine, which regulates the main forms of expression of the will of the people and spheres of influence. With regard to mediated people’s power or representative democracy, it also has a long history and practice in the Ukrainian legal tradition, which is implemented primarily in the process of formation of local self-government bodies. It was established that the protection of the principles of people’s power should become a priority task today, which is also important in the context of Ukraine’s European integration aspirations. Scientific novelty. The ways of development of people’s power in Ukraine are followed; the differences between direct and indirect people’s power are specified; singled out problematic areas of national legislation that inhibit the development of people’s power in our time. Practical significance. The results of the research can be used in further theoretical-legal and historical-legal studies, preparation of special courses, reform of local self-government bodies.